2011
DOI: 10.5402/2011/653246
|View full text |Cite
|
Sign up to set email alerts
|

Secondary IOL Implantation without Capsular Support: A Laser Flare Cell Meter Study

Abstract: Phacoemulsification and the contemporary implantation of intraocular lens (IOL) within the capsular bag represent the standard of care in cataract surgery, but sometimes a primary IOL implant is not possible due to intraoperative complications or preexisting conditions so that a secondary implantation of IOL within the anterior or posterior chamber is necessary. The aim of our study was to assess the degree of inflammation due to a secondary implant of claw lenses, angle-supported IOLs, and scleral-fixated IO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The best method is one that offers best visual outcome with lowest complication in an already delicate situation. Each of the available options has its own risks and complications: transscleral fixation of posterior chamber IOLs has the advantage of posterior position of IOL, but it is a time-consuming procedure with known complications 9,10…”
Section: Discussionmentioning
confidence: 99%
“…The best method is one that offers best visual outcome with lowest complication in an already delicate situation. Each of the available options has its own risks and complications: transscleral fixation of posterior chamber IOLs has the advantage of posterior position of IOL, but it is a time-consuming procedure with known complications 9,10…”
Section: Discussionmentioning
confidence: 99%
“…The elevated IOP might be directly caused by prolonged inflammation or indirectly due to prolonged corticosteroid use. The Laser Flare Cell Meter Study by Cellini et al 29 compared the severity of intraocular inflammation among ACIOL, SFIOL, and iris-fixated IOL using a laser cell flare meter, which is a more objective and quantitative measurement. The results demonstrated that SFIOL had significantly more severe subclinical intraocular inflammation than the other two IOLs up to 90 days.…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrated that SFIOL had significantly more severe subclinical intraocular inflammation than the other two IOLs up to 90 days. 29 The eye that underwent glaucoma drainage device implantation was diagnosed preoperatively as primary angle-closure suspect. The narrowed anterior chamber angle might be further compromised in subclinical intraocular inflammation after surgery, causing persistent IOP elevation.…”
Section: Resultsmentioning
confidence: 99%
“…However, they are technically challenging to insert, with an increased risk of IOL tilt, intraocular hemorrhage, suture breakage, and endophthalmitis. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%